Priests of the law: Roman law and the making of the common law's first professionals - McSweeney, Thomas J. (Oxford legal history series, 2020)
This volume examines the development of legal professionalism in the early English common law, with specific reference to the 13th-century treatise known as Bracton and to its likely authors.